There is no evidence that the forest service's goshawk recommendations improve goshawk nest productivity - Paul Beier; Michael F. Ingraldi (Wildlife Society Bulletin, 2012)
Abstract Several years ago we tested whether goshawk (accipiter genitilis) productivity increased with increasing similarity of goshawk breeding areas to Forest Service recommendations for the northern goshawk in the southwestern United States. Surprisingly, we found that nest productivity declined as similarity to the recommendations increased from 21% to 57% (Beier et al. 2008). Reynolds et al. (2012) argued that this pattern may have been the result of flawed measurements and analyses, and suggested alternative methods and analyses. Although their suggestions have merit, it is unlikely such changes would have altered the negative trend we observed. Reynolds et al. (2012) also argued that goshawk reproduction might increase as similarity with Forest Service recommendations increases from 57% to 100%. We agree that a larger sample of breeding areas, spanning the full spectrum of similarity to the recommendations, would provide a more powerful evaluation of the recommendations. We suggest that the Forest Service conduct such an evaluation using data for all or some of the 121 breeding areas they have monitored for 8–19 years each. © 2012 The Wildlife Society.